JOB CHARACTERISTICS RELATED STRESS AS A RISK FACTOR OF STROKE: A LITERATURE REVIEW - Sri Yuliana (Universitas Fort De Kock, 2021)
Abstract: Individuals may get the stress from everywhere which contact with them including the workplace. The aim of this study is to describe and update the empirical literature regarding job characteristic related stress as the risk factor of stroke both in woman and man workers. This review literature including studies published between 2009 until 2018. We searched by an electronic database including PUBMED, Web of Science and search engine Google scholar using several keywords related job stress. Analyzing data was used PCOT (Population, conclusion, outcome and time) for general questions and was assessed continuously in order to make better judgments about the value of each article. A literature search was performed nine studies from different countries. Many factors induced the job stress which correlated the risk factors of stroke. Eight studies reported high job strain had association with the risk factor of stroke which is psychological pressure, excessive work, sitting and inconsistency of work. In contrast, there are two studies had a negative association between job strain and risk factor of stroke. High demand and low job control were causes the high job strain in the worker population. The company have to focus on regular check-up of workers.